Peritoneal Washing Cytology Positivity in Gastric Cancer: Role of Lymph Node Metastasis as a Risk Factor - Kim, Sojung; Lee, Han Hong; Song, Kyo Young; Seo, Ho Seok (Journal of gastric cancer, 2024)
Peritoneal washing cytology (PWC) is a widely used diagnostic tool for detecting peritoneal metastasis of advanced gastric cancer. However, the prognosis of patients with positive PWC remains poor even after gastrectomy, and treatments vary among institutions and eras. In this study, we identified the clinical factors that can help predict cytology-positive (CY(+)) gastric cancer. We retrospectively reviewed the national data of patients with gastric cancer from 2019, as provided by the Information Committee of the Korean Gastric Cancer Association. Of the 13,447 patients with gastric cancer, 3,672 underwent PWC. Based on cytology results, we analyzed the clinicopathological characteristics and assessed the possibility of CY(+) outcomes in relation to T and N stages. Of the 3,270 patients who underwent PWC without preoperative chemotherapy, 325 were CY(+), whereas 2,945 were negative. CY(+) was more commonly observed in patients with Borrmann type IV gastric cancer, an undifferentiated histological type, and advanced pathological stages. Multivariate analysis revealed Borrmann type IV (odds ratio [OR], 1.821), tumor invasion to T3-4 (OR, 2.041), and lymph node metastasis (OR, 3.155) as independent predictors of CY(+). Furthermore, for circular tumor location, the N stage emerged as a significant risk factor for CY(+), particularly when the tumor was located on the posterior wall (PW) side. Lymph node metastasis significantly affects CY(+) outcomes, particularly when the tumor is located on the PW side. Therefore, PWC should be considered not only in suspected serosal exposure cases but also in cases of lymph node metastasis.